PEMBELAJARAN MEDAN MAGNET MENGGUNAKAN METODE SIMULASI MODEL ISING 2D - Faradiba Faradiba (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2015)
This research was conducted as an alternative learning for the study of the magnetic field using the 2D Ising Model with simulation method. The programs are written in macro language and ran in ImageJ software. The research of designing a system size namely 32 x 32, energy and magnetization are measured as functions of temperature. Simulation conducted to see the magnetic momen when temprature is changed on the system. It is found that for low temperature regime, the absolute magnetization close to 1, which means tha tall spins are in the homogeneous state. By the increase the temperature close to the critical one = 2,3, the magnetization decrease drastically into zero. For the energy, low temperature regime gives the low energy. By the increase the temperature, the energy increase drastically near the critical temperature, and finally close to zero for high temperature regime. The state of the system is changed from ferromagnetic into the paramagnetic.Keywords : Magnetic Field, Magnetization, Energy, 2D Ising Model, Learning.